Peran Kiai Dalam Membentuk Karekter Humanis Religius pada Mahasantri - Muwirotus Solehah; Muru’atul Afifah (Pusat Riset dan Inovasi Nasional, 2024)
Moral decadence in Indonesia is a familiar problem, especially among teenagers, which has recently disturbed teachers and parents, as has been widespread on various social media about deviant behavior carried out by teenagers nowadays. Now. In this way, the government provides a solution by implementing character education in educational institutions. Religious humanist character education is a teaching process to develop potential that is oriented towards the whole person by paying attention to aspects of responsibility in relationships with humans and relationships with God so that they have religious spiritual strength, individual piety which is needed by the self, the nation's community and the state. In the Islamic boarding school environment, kiai have an important role in forming the character of each student. The object of research in this research is the role of Kiai Mujammi; Abdul Musyfie in forming Religious Humanism among students at Ma'had IDIA Prenduan. In this research, the researcher addresses the problem in 1. What is the concept of the religious humanist character of KH. Mujammi' Abdul Musyfie, 2. What is the role of Kiai Mujammi' in forming a religious humanist character in the IDIA ma'had? This research uses a qualitative-descriptive research method, by collecting data through observations, interviews and documentation. This research uses the Miles and Huberman model analysis method. The results of this research are the concept of KH's religious humanist character. Mujammi' Abdul Musyfie is guided by the book of Siroh Nabawiyah in which Rasulullah SAW always treated other people as brothers.